Effect of lead filters on the performance of a neuro-pet tomograph operated without Septa - Spinks, Terry Jones; Sayed, Inayatullah Shah (IEEE, 1993)
The value of using lead filters to improve the quality of PET data has been investigated for a CTI/Siemens 953B brain scanner operated without septa. The filters consisted of sheets of thickness 0.5mm and 1.0mm and axial width 18cm which were placed around the outer surface of the patient port. The port diameter is 35 cm and the axial FOV 10.65cm. The ratios of dead times (with/without filter) with lmCi (20cm uniform cylinder) in the FOV are 0.92 (0.5mm) and 0.82 (1mm) at a lower threshold (LLD) of 380keV; the values at 15OkeV are 0.87 and 0.76. Randoms rates are reduced by 12% (0.5mm)and 27% (1mm) at a LLD of 38OkeV and by 20% and 40% at 150keV. These values reflect the significant reduction of lower energy events observed in the measured energy spectrum. However, these reductions are accompanied by a drop in the true coincidence rate such that NEC is reduced for count rates up to the maximum measured trues rate at lower thresholds of 380 keV and 150 keV. It is concluded that the filters used in this study provide no advantage in the performance of the tomograph.